Using film to enhance students’ discussion of sociocultural issues - Vlasenko, Ludmila; Trygub, Inna (My University, 2012)
This article introduces a technique for designing a course which utilizes film to enhance students’ discussion of sociocultural issues. The article gives some background into theory behind content-based learning.
Keywords: соціокультурні теми; спілкування іноземною мовою; навички; социокультурные темы; обсуждения на английском; навыки; sociocultural issues; discussions in English; skills; кафедра ділової іноземної мови та міжнародної комунікації